Galectin-3 and Estrogen Receptor Alpha as Prognostic Markers in Prolactinoma: Preliminary Results From a Pilot Study - Bima, Chiara; Chiloiro, Sabrina; Giampietro, Antonella; Gessi, Marco; Mattogno, Pier Paolo; Lauretti, Liverana; Anile, Carmelo; Rindi, Guido; Pontecorvi, Alfredo; De Marinis, Laura; Bianchi, Antonio (Frontiers in Endocrinology, 2021)
Introduction Prolactin-secreting pituitary tumors (PRL-omas) are generally benign neoplasia. However, a percentage of cases show aggressive behavior. Prognostic markers may allow for the identification of aggressive cases. In this study, we investigated the prognostic role of galectin-3 and the estrogen receptor alpha (ERα), as predictive biomarkers of aggressiveness and poor prognosis. Patients and Methods A mono-centric and retrospective study was conducted on consecutive cases of PRL-omas that underwent first line treatment with surgery and were followed-up for at least five years. The immunohistochemical expression of ERα and galectin-3 was investigated in each case. Results 36 patients were enrolled. Galectin-3 resulted positive in 11 patients (30.6%). The median expression of ERα was 85% (IQR: 37). Among the group of 21 patients who underwent radical surgery (58.3%), recurrence occurred in 12 cases (33.3%). 27 patients were treated post-surgery with a dopamine agonist (DA) (12 for recurrence and 22 for a history of partial surgery). 13 patients (48.1%) were responsive to DA. Six of 11 cases positive for galactin-3 underwent partial surgery (54.5%, p<0.001). Recurrence occurred in all five cases that underwent radical surgery, which were also positive for galectin-3 (p=0.03). Galectin-3 resulted positive in 9 patients resistant to DA treatment (81.1%, p=0.01). ERα expression was lower in tumors positive for galectin-3 (p<0.001), with mitotic activity (p=0.012), with higher Ki67 Li (p<0.001), and in males with post-surgical recurrence (p<0.001). Conclusion Galectin-3 and ERα play as markers of aggressiveness and prognosis in PRL-omas and may be tested to identify the aggressive forms of the disease.